Manajemen Peserta Didik Berbasis Asrama: Peran Pembimbing dalam Penguatan Disiplin Santri - Naily Fauziyah; Muh. Hanif (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study aims to analyze the role of dormitory supervisors in student management to improve the discipline of male students at the Miftahul Huda Majenang Islamic Boarding School. The focus of the study is directed at the guidance strategies, supervision patterns, and mechanisms for managing students' daily activities as part of student management practices at the Islamic boarding school. This study uses a qualitative approach with a descriptive-analytical design through observation, interviews, and documentation techniques. The research results show that student discipline is formed through the integration of three main elements: intensive, role-model-based guidance, a structured, multi-layered supervision system, and consistent time management. Complex supervisors act as key actors connecting institutional rules with students' daily practices, so that discipline is not merely coercive but internalized in students' behavior. These findings indicate that the effectiveness of student management in Islamic boarding schools is largely determined by a combination of structural controls and cultural approaches. This study concludes that the role of dormitory supervisors is a strategic element in building a sustainable student discipline system. Theoretically, this research contributes to the development of Islamic boarding school-based student management studies by offering an integrative model of guidance, supervision, and role modeling. Practically, these findings can serve as a reference for Islamic boarding schools in designing effective discipline management systems.